The Influence of Electronic Word of Mouth (E-Wom), Brand Image and Product Quality on Buying Interest in Vivo Smartphones in Jakarta - Arif Setiawan; Bernadin Dwi M; Maria Assumpta Wikantari (International Journal of Asian Business and Management, 2024)
This study is a quantitative research on Consumer Purchase Intention for Vivo Smartphones. The purpose of this research is to determine the effect of independent variables, namely Electronic Word of Mouth (E-WOM), Brand Image, and Product Quality, on the dependent variable, which is Purchase Intention. The population of this study consists of consumers who are aware of and use Vivo smartphones in Jakarta, with a sample size of 126 respondents selected using a non-probability sampling method. This research employs purposive sampling based on predefined criteria. The data for this study were obtained from an online questionnaire (Google Form) distributed to consumers in Jakarta who use and are aware of Vivo smartphones. For data analysis, the author used descriptive and inferential analysis techniques processed through SmartPLS 3.2.9. The study results indicate that (1) Electronic Word of Mouth does not have a positive and significant effect on Purchase Intention, with a path coefficient value of 0.021. (2) Brand Image has a positive and significant effect on Purchase Intention, with a path coefficient value of 0.215. (3) Product Quality has a positive and significant effect on Purchase Intention, with a path coefficient value of 0.593